Design and clinical application of the device for stone needle and scraping of auricular acupoint (耳部砭石刮痧器的制作及临床应用) - LI Ping (李萍); HUANG Yanping (黄砚萍) (中西医结合护理)
This paper introduced the design of the device for stone needle and scraping of auricular acupoint, and analyzed its clinical application in specific cases. The scraping technique and related acupoint were selected by syndrome differentiation before treatment. The combination treatment of stone needle and scraping therapy proved to be a safe and effective treatment. (本文主要介绍了耳部砭石刮痧器的制作和使用方法, 并分析相关案例。耳部砭石刮痧疗法融合了砭法和刮痧两种传统中医治疗方法, 根据辨证分型选择刮痧方法和作用部位, 是一种安全有效的治疗方法。)